2012
DOI: 10.1007/s11999-011-1994-8
|View full text |Cite
|
Sign up to set email alerts
|

Odontoid Fractures With Neurologic Deficit Have Higher Mortality and Morbidity

Abstract: Level III, prognostic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 20 publications
0
11
1
1
Order By: Relevance
“…In the full text of the included publications mortality data was identified and added to a cumulative database. In 29 articles mortality data from 1284 cases was available [ 3 , 5 , 6 , 11 15 , 18 21 , 24 – 27 , 31 36 , 41 44 , 46 , 50 ]. If a patient characteristics chart was available, survival, follow-up, patient age, and treatment allocated were added directly to the database for each patient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the full text of the included publications mortality data was identified and added to a cumulative database. In 29 articles mortality data from 1284 cases was available [ 3 , 5 , 6 , 11 15 , 18 21 , 24 – 27 , 31 36 , 41 44 , 46 , 50 ]. If a patient characteristics chart was available, survival, follow-up, patient age, and treatment allocated were added directly to the database for each patient.…”
Section: Resultsmentioning
confidence: 99%
“…Other factors than treatment modality seem to play a greater role for patient survival. Patel et al [ 50 ] found in their investigation of 20 elderly patients with type II odontoid fractures associated with neurological deficit a higher mortality (RR = 4.7; 95% CI: 1.4–16.6) than in neurologically intact patients ( n = 188); in patients with complete tetraparesis ( n = 11) the risk was even higher (RR = 9.3; 95% CI: 1.2–73.0).…”
Section: Discussionmentioning
confidence: 99%
“…Some literature raises the concern that myelopathy may develop in patients with odontoid fracture and with odontoid nonunion. 40 , 53 56 In a retrospective institution database search by Patel et al, 57 it was found that neurologic deficit with type II odontoid fracture was as high as 9.6%. Kepler et al 56 performed a retrospective case series of 133 consecutive patients over a 5-year period with type II odontoid fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Cette proportion semble faible comparée aux données de certaines publications. Récemment, Patel retrouvait 9,6 % de déficits neurologiques associés aux fractures de l'odontoïde tous âges confondus (42-89 ans) avec une mortalité associée élevée puisque 50 % étaient décédés dans les trois premiers mois [50].…”
Section: Discussionunclassified